Diplomatic Tensions in the South China Sea: Implications for Regional Stability - Kunkunrat (International Publisher, 2024)
Diplomatic tensions in the South China Sea have become a major concern in global geopolitical dynamics. Conflicts of interest and policy dynamics involving the coastal countries of the South China Sea have made this region always volatile at any time. This research aims to analyze the root causes of these tensions and identify possible implications for regional stability. The research method used in this research is a qualitative method with a descriptive approach. The results of this research reveal that diplomatic tensions in the South China Sea have a serious impact on regional stability. Disputes related to territorial claims, Exclusive Economic Zones, and economic disputes create economic and security vulnerabilities that can harm all parties involved. Impeded multilateral cooperation also hinders efforts to resolve joint issues. In addition, social and political impacts create internal instability that can trigger riots and divisions within the government. Thoughtful handling of these tensions is necessary, involving open dialogue, intelligent diplomacy, and a strong commitment to maintaining regional stability, creating a strong foundation for sustainable peace and security in the South China Sea